Nonparametric estimators for varextropy under $α$-mixing condition with appliction in exponential AR(1) model - Raheleh Zamini; Faranak Goodarzi; Mohamad Salimi (Journal of Mahani Mathematical Research)
The goal of this paper is to study the problem of estimation of varextropy function under $α$-mixing dependence condition. We propose nonparametric estimators for varextropy, residual varextropy and past varextropy. Asymptotic properties of the proposed estimators are investigated under regularity conditions. Moreover, the comparison of the proposed estimators for varextropy in terms of the bias and mean squared error has been done by Monte Carlo method. Furthermore, a real data example is presented.